2014
DOI: 10.1007/s10877-014-9635-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided bilateral cervical plexus block reduces postoperative opioid consumption following thyroid surgery

Abstract: Thyroid surgery may cause severe postoperative pain and discomfort for patients. Superficial cervical plexus block (SCPB) is one of the regional anesthesia techniques that can provide postoperative analgesia for thyroid surgery. The purpose of this study was to evaluate analgesic effect of ultrasound (US) guided SCPB in patients undergoing thyroid surgery. Fifty ASA I-II patients, aged 20-60, were included in this single blinded study. In a randomized and prospective manner patients were allocated to either SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 24 publications
0
38
0
7
Order By: Relevance
“…Similarly, Gurkan et al’s4 study also concluded that US-guided bilateral superficial cervical plexus block has a significant analgesic effect in patients undergoing thyroid surgery.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Similarly, Gurkan et al’s4 study also concluded that US-guided bilateral superficial cervical plexus block has a significant analgesic effect in patients undergoing thyroid surgery.…”
Section: Introductionmentioning
confidence: 84%
“…However, the study by Eti et al11 showed that bilateral superficial cervical plexus block did not decrease analgesic requirement after thyroid surgery. Gurkan et al4 in their study concluded that ultrasound-guided bilateral superficial cervical plexus block had a significant analgesic effect in patients undergoing thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Gurkan and colleagues [17] performed a study to assess the analgesic effect of US guided BSCPB in patients undergoing thyroid surgery; fifty patients were assigned to either SCPB or no block. Bilateral SCPB was done before surgery using US with 10 ml 0.25% bupivacaine for each side.…”
Section: Discussionmentioning
confidence: 99%
“…Hastaya sırtüstü pozisyonda ultrason eşliğinde 10 ml %0,25 bupivakain ve 10 ml %2 lidokain kullanılarak Gürkan ve ark. [3] tarif ettiği şekilde YSP uygulandı. USG'un lineer probu (10-18 MHz Esaote My Lab 5, Geneva, İtalya) kullanılarak pleksus, sternokleidomastoid kas (SKM)'in hemen derinlerinde küçük hipoekoik yapılar olarak görüntülendi (Şekil 1, 2a…”
Section: Olgu Sunumuunclassified